Use of Dairy and Plant-Derived Lactobacilli as Starters for Cherry Juice Fermentation - Ricci, Annalisa (Nutrients, 2019)
Background: Lactic acid bacteria (LAB) exhibit a great biodiversity that can be exploited for different purposes, such as to enhance flavours or metabolize phenolic compounds. In the present study, the use of dairy and plant-derived LAB strains to perform cherry juice fermentation is reported. Methods: The growth ability of Lactobacillus plantarum, Lactobacillus casei, Lactobacillus paracasei and Lactobacillus rhamnosus was studied in cherry juice. Profiling of sugars, organic acids and volatile compounds was performed by GC-MS (Gas Chromatography-Mass Spectrometry), while the phenolic fraction was characterized using UHPLC (Ultra High Performance Liquid Chromatography) equipped with a linear ion trap-mass spectrometer. Results: Sucrose significantly decreased in all fermented samples as well as malic acid, converted to lactic acid by malolactic fermentation. The total amount of volatile compounds increased. Specifically, propyl acetate, an ester with fruit notes, reached the highest concentration in L. rhamnosus and L. paracasei (dairy strains) fermented juices. Phenolics were extensively metabolized: caffeic acid was converted into dihydrocaffeic acid, p-coumaric acid into 4-ethylphenol and phenyllactic acid was produced. Conclusion: Lactic acid fermentation confer fruit notes to the juice and enhance phenyllactic acids, especially employing dairy strains (L. rhamnosus and L. paracasei). The level of dihydrocaffeic acid, a compound with putative biological activity was also increased (in particular with L. plantarum).